Information System Design Realization and Performance Achievements of the Manpower Office of Kuantan Singingi District - Agung Apri Denta; Helpi Nopriandi; Erlinda Erlinda (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2024)
Performance data collection is directed at obtaining accurate, complete, timely and consistent performance data that is useful for decision making in order to improve the performance of Government agencies without abandoning the principles of balancing costs and benefits, efficiency and effectiveness. Kuantan Singingi Regency Manpower Office, so far the reporting and data recapitulation process has been carried out manually using the Microsoft Office application. This has resulted in frequent data overlaps and difficulty in reporting performance data. Therefore, an information system for the realization and performance achievements of the Kuantan Regency Manpower Office is needed. singing becomes more effective and efficient.